Correlation of Early-Onset and Late-Onset Preeclampsia with Increased Lactic Dehydrogenase Serum Levels - Kezia Sitorus, Lois Tabitha; Priyanto, Edy; Zulvayanti, Zulvayanti (Indonesian Journal of Obstetrics & Gynecology Science, 2024)
Introduction: Preeclampsia is a hypertensive disorder during pregnancy that is associated with 2-8% of pregnancy-related complications worldwide. Lactate Dehydrogenase (LDH) is a dominant intracellular cytoplasmic enzyme of anaerobic glycolysis and is released into the general circulation during cell death. This enzyme is increased in preeclampsia due to glycolysis and chronic anoxemia due to placental ischemia. The effect of LDH on pregnancy-related complications, such as preeclampsia, is now gaining attention. This study aims to assess the difference in LDH serum levels in early- and late-onset preeclampsia. Methods: This is an analytical observational study with a retrospective approach and cross-sectional design. The sample consists of 106 patients with early- and late-onset preeclampsia at RSUD Prof Dr. Margono Soekarjo from July to December 2022. Data analyzed in this study was collected from medical records.Results: This study found that 65.09% of the subjects were less than 35-years-old, 76.42% were multiparous, 64.15% had term birth, and 77.01% had a BMI >30. The mean LDH level in early-onset preeclampsia was 292.38 + 255.05 (141–1507), while the mean in late-onset preeclampsia was 181.60 + 43.13 (103–319). The cut-off value for LDH levels in preeclampsia patients was 185.5 U/L. A significant correlation was found between mean BMI and LDH levels (p=0.0001) and between mean maternal age and LDH levels (p=0.0001).Conclusion: There was a significant relationship between the onset of preeclampsia, mean BMI, and mean maternal age and LDH levels.Hubungan antara Kejadian Preeklamsia Awitan Dini dan Lanjut dengan Peningkatan Serum Laktat DehidrogenaseAbstrakPendahuluan: Preeklamsia adalah kelainan hipertensi pada kehamilan yang berhubungan dengan 2 – 8% komplikasi terkait kehamilan di seluruh dunia. Laktat dehidrogenase (LDH) adalah enzim sitoplasma intraseluler dominan dari glikolisis anaerobik dan dilepaskan ke sirkulasi umum selama kematian sel. Enzim ini meningkat pada preeklamsia akibat glikolisis dan anoksemia kronis akibat iskemia plasenta. Pengaruh LDH terhadap komplikasi terkait kehamilan seperti preeklamsia kini mulai mendapat perhatian. Studi ini bertujuan untuk menilai perbedaan kadar serum LDH pada preeklamsia awitan dini dan lanjut.Metode: Penelitian ini merupakan penelitian observasional analitik dengan pendekatan retrospektif dan desain potong lintang. Sampel terdiri atas 106 pasien dengan preeklamsia awitan dini dan lanjut di RSUD Prof Dr. Margono Soekarjo periode Juli-Desember 2022. Data diperoleh dari rekam medis.Hasil: Ditemukan bahwa 65,09% subjek berusia kurang dari 35 tahun, sebanyak 76,42% subjek multipara, sebanyak 64,15% subjek mengalami kelahiran aterm, sebanyak 77,01% subjek memiliki IMT >30. Rerata kadar LDH pada preeklamsia awitan dini ditemukan 292,38 + 255,05 (141–1507), sedangkan rerata pada preeklamsia awitan lanjut adalah 181,60 + 43,13 (103–319). Nilai cut off kadar LDH pada pasien preeklamsia ditemukan 185,5 U/L. Hubungan signifikan ditemukan antara rerata IMT dengan kadar LDH (p=0,0001) dan rerata usia ibu dengan kadar LDH (p=0,0001).Kesimpulan: Terdapat hubungan signifikan antara awitan preeklamsia, rerata IMT dan rerata usia ibu dengan kadar LDH.Kata kunci: preeklamsia, lactic dehydrogenase, preeklamsia awitan dini, preeklamsia awitan lanjut